Rapid Communication: Cardiac and skeletal muscle myosin exert procoagulant effects - Coleman, Julia R (Shock, 2019)
INTRODUCTION: Trauma-induced coagulopathy (TIC) and the tissue injury-provoked procoagulant profile are prevalent in severely injured patients, but their mechanisms remain unclear. Myosin, exposed by or released from tissue injury, may play a role in promoting thrombin generation and attenuating fibrinolysis. The objective of the study is to examine the effects of cardiac and skeletal muscle myosins on coagulation in whole blood using thrombelastography (TEG). MATERIALS AND METHODS: Whole blood was collected from healthy adult volunteers (n=8) and native TEGs were performed to evaluate the global coagulation response in the presence of cardiac or skeletal muscle myosin by measuring reaction (R) time (minutes), clot angle (°), and maximum amplitude (MA, mm). TEG measurements were compared using paired t-tests. RESULTS: Cardiac and skeletal muscle myosins decreased R, from 10.8 min to 8.0 min (p<0.0001) and 6.9 min (p=0.0007), respectively. There were no effects observed on clot propagation (angle) or clot strength (MA) with myosin addition. In the presence of tPA, both cardiac and skeletal muscle myosins shortened R from 11.1 min to 8.62 min (p=0.0245) and 7.75 min (p=0.0027), respectively), with no changes on angle or MA. CONCLUSIONS: Cardiac and skeletal muscle myosins exhibit procoagulant effects in TEG assays. These whole blood TEG results support the hypothesis that cardiac and skeletal muscle myosins may be either pro-hemostatic or prothrombotic depending on context.